Analisis Wacana Iklan Pada E-Commerce Shopee Big 6.6 Great Mid-Year Sale - Chindi Gracefva Purba; Indah Rosa Damanik; Putri Azhari; Sunarti Sunarti; Mustika Wati Siregar (Pusat Riset dan Inovasi Nasional, 2024)
Online shopping has become an activity carried out by many groups, one of which is Shopee. Shopee is an e-commerce application which was launched in December 2015 by PT. Shopee Indonesia can foster the entrepreneurial spirit of sellers in Indonesia. Discourse analysis aims to determine the existence of patterns or order expressed by a text. The interpretation of a linguistic unit can be known clearly, including the message to be conveyed, why it must be conveyed, and how the message is conveyed. This research uses a content analysis method with a qualitative approach.